2013
DOI: 10.1055/s-0033-1347365
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Blood Flow by Doppler Ultrasound: The Impact of Gestational Age and Time from First Enteral Feeding in Preterm Neonates

Abstract: There were significant differences in PSV by GA group. SMA PSV change after feeding was lower in patients who had feeding intolerance compared with those who did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Despite increases in blood flow during the first weeks of life, splanchnic oxygen saturation (r s SO 2 ), estimated using near-infrared spectroscopy (NIRS), initially decreases in the first week of life and then increases until day 21 after birth ( 83 , 84 , 86 88 ). Advancing gestational age (GA) is associated with both higher blood flow and higher r s SO 2 ( 78 , 80 , 84 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite increases in blood flow during the first weeks of life, splanchnic oxygen saturation (r s SO 2 ), estimated using near-infrared spectroscopy (NIRS), initially decreases in the first week of life and then increases until day 21 after birth ( 83 , 84 , 86 88 ). Advancing gestational age (GA) is associated with both higher blood flow and higher r s SO 2 ( 78 , 80 , 84 ).…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis is supported by findings of Ledo et al (87) who investigated the effect of ductal patency on the course of r s SO 2 in preterm neonates and found that the increases in r s SO 2 from day 3 of life are paralleled by ductal closure. The initial decrease in r s SO 2 may thus be explained by ductal steal, resulting in reduced diastolic flow in the descending aorta, resulting in a decreased intestinal perfusion pressure, and in the absence of intestinal pressure-flow regulation, preterm intestine relies on increases in oxygen extraction (73,74,80,82,87). This may enable preterm neonates to meet intestinal oxygen requirements during baseline conditions, yet creates unfavorable conditions during periods of additional stress.…”
Section: Interpretation and Discussionmentioning
confidence: 99%